INVENTAIRE ET DISPONIBLITE DES PLANTES MEDICINALES DANS LA FORÊT CLASSÉE DE YAPO-ABE, EN COTE D’IVOIRE - Piba Serge Cherry; Tra Bi Fezan Honora; Konan Djézou; Bitignon Bley Guy Alain; Bakayoko Adama (European Scientific Journal, ESJ, 2015)
In Ivory Coast, the increasing demand for vegetable drugs brings to estimate the availability and distribution of sources of NTFPs species for medicinal use. This study, conducted in the classified forest of Yapo-Abbé and surrounding rural areas and based on ethnobotanical surveys coupled with floristic inventories by the methods of surface surveys, allowed to inventory 47 medicinal species sources of NTFPs. The predominant morphological type is the tree (85%). Trunk bark up the majority of harvested vegetable drugs (81%), whereas, the graze after cutting down of the plant is the mode of the most used collection. The preferential species source of NTFPs of the region are: Annickia polycarpa (UV = 2.24), Landolphia owariensis (UV = 2.08), Khaya ivorensis (UV = 2.06), etc. With, on average, an individual.ha-1 , these species are poorly represented in the classified forest of Yapo-Abbé. A single preferential ligneous species is strongly represented: Uapaca esculenta, with an average density of 5.56 ± 5.72 (ind.ha-1 ). Also, the reforested areas have the highest densities in medicinal plants. The species rarity-weight richness index defined Landophia hirsuta (Ri = 93.43%), Ricinodendron heudelotii (Ri = 84.02%), Salacia nitida (Ri = 89.39%) and Landolphia owariensis (Ri = 81.81%) as rare species in Yapo-Abbé forest. This study also showed that the sustainable management of forests and their enrichment of medicinal species undergoing strong anthropogenic pressures, should be favored to improve the availability of medicinal plants.